2003
DOI: 10.1038/sj.jhh.1001614
|View full text |Cite
|
Sign up to set email alerts
|

Lercanidipine vs lacidipine in isolated systolic hypertension

Abstract: This randomised, double-blind, double-dummy, parallel group, multicentre study compared the efficacy and tolerability of lercanidipine with lacidipine. Elderly patients with isolated systolic hypertension (supine blood pressure X160/o95 mmHg) were enrolled and underwent a placebo run-in period of 14-27 days before random allocation to lercanidipine tablets 10 mg once daily (n ¼ 111) or lacidipine tablets 2 mg once daily (n ¼ 111) for the assessment period (112-160 days). Titration to lercanidipine 20 mg once d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
1
10
0
1
Order By: Relevance
“…Lercanidipine has shown different effects on plasma norepinephrine levels and a lower sympathetic activation compared with other DHP (Fogari et al 2003; Grassi et al 1998;), what could, at least in part, explain the lower rate of leg edema observed with this drug when compared to amlodipine or nifedipine. These results are in concordance with those previously described in other clinical trials (Agrawal et al 2006; Barrios et al 2002; Barrios et al 2006a; Barrios et al 2006b; James et al 2002; Leonetti et al 2002; Millar‐Craig et al 2003; Viviani 2002; Pedrinelli et al 2003; Romito et al 2003). Nevertheless, in most of these studies, the dose of lercanidipine initially used was 10 mg per day (considered low dose in our study) and it was titrated to 20 mg only if necessary.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Lercanidipine has shown different effects on plasma norepinephrine levels and a lower sympathetic activation compared with other DHP (Fogari et al 2003; Grassi et al 1998;), what could, at least in part, explain the lower rate of leg edema observed with this drug when compared to amlodipine or nifedipine. These results are in concordance with those previously described in other clinical trials (Agrawal et al 2006; Barrios et al 2002; Barrios et al 2006a; Barrios et al 2006b; James et al 2002; Leonetti et al 2002; Millar‐Craig et al 2003; Viviani 2002; Pedrinelli et al 2003; Romito et al 2003). Nevertheless, in most of these studies, the dose of lercanidipine initially used was 10 mg per day (considered low dose in our study) and it was titrated to 20 mg only if necessary.…”
Section: Discussionsupporting
confidence: 93%
“…This drug has a slow onset of action due to its high lipophilicity and its partitioning into the lipid bilayer of cell membranes, followed by diffusion to the receptor binding site, that helps to avoid reflex tachycardia associated with other DHP, such as nifedipine (Ambrosioni and Circo 1997; Meredith 1999). Its efficacy has been evaluated in noncomparative (Barrios et al 2002; Viviani 2002; Barrios et al 2006a; Barrios et al 2006b) and comparative studies (Agrawal et al 2006; James et al 2002; Millar‐Craig et al 2003;). In most trials the starting dose was 10 mg/day.…”
Section: Introductionmentioning
confidence: 99%
“…[ 53 ] The antihypertensive effect is maintained for 24 h, with a favorable smoothness index and a significant decrease of morning BP rise as well as BP variability [ Figure 3 ]. [ 51 54 55 56 57 ]…”
Section: A Ntihypertensive a Ctivitymentioning
confidence: 99%
“…При изучении пожилых больных с изолированной систолической АГ сходные данные были получены как в плацебо-контролируемом исследовании, так и в сравнительном с лацидипином [24].…”
Section: лерканидипин в пожилом возрастеunclassified